ANALISIS IMPLEMETASI KAJIAN ISLAM TERKAIT AL-’AMAL WA AL-SANA’ DALAM BERDAGANG - Amsari, Syahrul; Anggara, Windu; Shawab, Nabil; Tarigan, Azhari Akmal (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2023)
Trading without faith and charity only raises miserliness and greed in humans. To reduce this problem, the Al-Qur'an has provided instructions on how to trade correctly in order to earn the pleasure of Allah SWT. So that the discussion does not touch on a broader domain, the author focuses on how Islamic studies in the Al-Qur'an and hadith literature analyze implementational-amal wa al-sana’in trading. This study uses the literature review method in analyzing editorials amal and too much in trading based on an Islamic point of view. Based on an in-depth study using an interpretive approachMaudhu'iin understanding the context of the Qur'an through the verses related to the termal-amal wa al-sana’in trading. The results of the study conducted, obtained the implementation of related Islamic studies al-mal wa al-sana’in trading in relation to God's loving and generous attributes to create a prosperous and humane life as an orientation in trading activities using the concept of faith and righteous deeds in order to obtain blessings, pleasure and safety from Allah SWT in this world and also in the afterlife for every human being carry out Islamic law.